Stub-Based Higher Order Harmonics Suppression for Upper W-LAN Band Microstrip Patch Antenna - Batabyal, Surajit Batabyal; Deb Roy, Subhadra; Laxmi Koley, Bijoy; Mukherjee, Moloy (Journal of Neonatal Surgery, 2025)
In this paper, the authors investigate the elimination of higher order harmonics in a microstrip patch antenna operating in higher bands for wireless local area networks (WLAN). The goal will be the subsequent suppression of harmonics without further complication of the design by either introducing additional structures or filters, while the stub is included in the design. The report presents the methodol- ogy employed, which involves designing and simulating a microstrip patch antenna with stubs strategically placed at specific locations. The outcomes show how successful the suggested technique in reducing the higher-order harmonics, leading to improved antenna performance. The findings highlight the importance of stub placement and dimensions in achieving desired harmonic suppression. Based on the results, recommendations are provided for optimizing stub configurations to further enhance the elimination of higher-order harmonics in microstrip patch antennas operating in W-LAN higher bands. This research advances the creation of compact and efficient antenna designs for modern wireless communication systems.